The use of antibiotics at shipping time to suppress the occurrence of respiratory complex in cattle. - Koch, B.A.; Smith, E.F.; Richardson, D.; Cox, R.F.; Smith, J.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
One of the major problems confronting cattlemen is control of the occurrence of respiratory diseases such as shipping fever, colds, nasal congestion. and pneumonia. These respiratory conditions are especially troublesome to cattle feeders who ship and receive cattle during the fall and winter months, when adverse weather conditions put added stress on cattle. This study is to investigate the value of various antibiotics administered orally or by injection to weaning calves to control the occurrence of respiratory diseases during the first few weeks they are in drylot.
Keywords: Beef; Respiratory; Antibiotics; Shipping time